PSYCHOLOGY OF COLOR AND COLOR THERAPY: रंगों का मनोविज्ञान एवं रंग चिकित्सा - Kumar, Ashok (International Journal of Research -GRANTHAALAYAH, 2014)
An important feature of our vision system is color vision (bsavavat tapepavad). Color is a psychological property of the person’s sensory sensation (chelbavaswahpbans chtvchavatjal), which originates when the brain receives information about the external / environment. Experts have described three psychological dimensions of color (chelbavaswahpbans kapumdeepvad), this three dimension is related to illumination with three physical properties ie wavelength, intensity and purity. All three psychological dimensions are color, intensity and purity. According to psychologists, there are three important phenomena related to color vision (chimdavumvadvad), hue color adaptation (sprung chirp हमारी दृष्टि तन्त्र की एक महत्वपूर्ण विशेषता रंग दृष्टि (ब्वसववत टपेपवद) है। रंग व्यक्ति की संवेदी अनुभूति का एक मनोवैज्ञानिक गुण (च्ेलबवसवहपबंस च्तवचवतजल) होता है, जिसकी उत्पत्ति तब होती है जब मस्तिष्क को बाह्या/वातावरण के बारे में सूचना प्राप्त होती है। विशेषज्ञों ने रंग की तीन मनोवैज्ञानिक विमाएंे (च्ेलबवसवहपबंस कपउमदेपवद) बताई हंै, यह तीनों आयाम रोशनी को तीन भौतिक गुणों अर्थात् तरंग दैध्र्य, तीव्रता तथा शुद्धता से संम्बन्धित है। वे तीनों मनोवैज्ञानिक विमाएंे वर्ण, तीव्रता तथा शुद्धता हैं। मनोवैज्ञानिकों के अनुसार रंग दृष्टि से संम्बन्धित तीन महत्वपूर्ण घटनाऐ (च्ीमदवउमदवद) हैय रंग अनुकूलन (ब्वसवनत ंकंचजंजपवद), रंग मिश्रण (ब्वसवनत डपगजनतम) तथा वर्णान्धता (ब्वसवनत इसपदकदमेे)